A two-tier eurozone or a euro of regions? A radical proposal based on Keynes's clearing union - Jan A. Kregel (Levy Economics Institute of Bard College, 2017)
In light of the problems besetting the eurozone, this policy brief examines the contributions of John Maynard Keynes and Richard Kahn to early debates over the design of the postwar international financial system. Their critical engagement with the early policy challenges associated with managing international settlements offers a perspective from which to analyze the flaws in the current euro-based financial system, and Keynes's clearing union proposal offers a template for a better approach. A system of regional federations employing a clearing system in which members either retained their own currency or used a common currency as a unit of account in registering debits and credits for settlement purposes would preserve domestic policy independence and retain regional diversity.
Keywords: 330; Banking principle; Bretton Woods; Clearing union; Creditor countries; Debtor countries; Euro; Eurozone; Gold standard; John Maynard Keynes